Evaluation of a K-5 mathematics program which integrates children's literature: classroom environment and attitudes - Mink, Deborah V. (Curtin University, 2002)
This thesis describes a one-year study of 120 fifth grade students whose teachers participated in a program entitled Project SMILE (Science and Mathematics Integrated with Literary Experiences). The purpose of the study was to investigate the extent to which the classroom implementation of Project SMILE positively influenced the classroom environment and student attitudes toward reading, writing and mathematics. This was accomplished by, first, facilitating a series of five professional development workshops with the teachers and, subsequently, asking these teachers to use the strategies with their students. Because Project CRISS (CReating Independence through Student-owned Strategies), the foundation of SMILE, had already proven to be successful nationwide for secondary students, this study focused on elementary (K-5) school students and their teachers. My evaluation of this unique program, that integrates children's literature and mathematics, focused on student attitudes and the nature of the classroom learning environment. My research represents one of the relatively few studies that have employed learning environment dimensions with students in the elementary school mathematics classroom as criteria of effectiveness in the evaluation of educational innovations. The My Class Inventory (MCI) and an adaptation of the 1988 NAEP (National Assessment of Educational Progress) Attitude Survey were administered to a sample of 120 Grade 5 students as measures of students' perceptions of the classroom learning environment and their attitudes. Qualitative data were composed of student and teacher interviews, classroom observations and work samples. Methodologically, my study supports previous research that successfully combined qualitative and quantitative methods of data collection.The learning environment and attitude scales exhibited satisfactory internal consistency reliability and discriminant validity; additionally, the actual form of most learning environment scales was capable of differentiating between the perceptions of students in different classrooms. The implementation of SMILE was found to have a positive impact on the students and classes of the teachers who participated in the inservice program. In particular, students' attitudes to mathematics and reading improved, and there was congruence between students' actual and preferred classroom environment on the scales of satisfaction and difficulty. Therefore, others can implement SMILE with confidence. As well, prior research was replicated in that students' satisfaction was greater in classrooms with a more positive learning environment, especially in terms of student cohesiveness.